Perhitungan Waktu Tunda pada Sistem Radar Sekunder dengan Menggunakan Metode TDOA (Time Different Of Arrival) - Nainggolan, Paskah Handikardo Benjamin; Darjat, Darjat; Christoyono, Yuli (Departemen Teknik Elektro, Universitas Diponegoro, 2011)
The detection of the position and trajectory of the rocket is very necessary in order to launch a rocket capable of running as expected. If the position and trajectory of the rocket is not monitored properly, it could be bad. Therefore, the solution needed to be able to monitor the position and trajectory of the rocket with a specific technical studies. As an initial step in monitoring the position of the rocket is to know the time delay during the process send and receive signals between the sending station with a radio wave receiver. In this thesis, carried out a simulation application of TDOA-trilateration algorithm to compute the time delay on the secondary radar system. Techniques to get a distance that is by finding the difference between the send and receive signals between the transceiver station with a radio wave transponder. After setting on the transceiver and the transponder is set, by setting send data, protocol, and then it will be obtained automatically scanning the time delay is expected. This technique is called TDOA (Time Different Of arrival). This process will be simulated with MatlabaR2008a. Keyword : TDOA, time delay, rockets, radio, transceiver, transponder.